Diagnostic value of radiological imaging pre‐ and post‐drainage of pleural effusions. Issue 2 (6th November 2015) - Corcoran, John P.; Acton, Louise; Ahmed, Asia; Hallifax, Robert J.; Psallidas, Ioannis; Wrightson, John M.; Rahman, Najib M.; Gleeson, Fergus V.
Abstract : Patients with an unexplained pleural effusion often require urgent investigation. Clinical practice varies due to uncertainty as to whether an effusion should be drained completely before diagnostic imaging. We performed a retrospective study of patients undergoing medical thoracoscopy for an unexplained effusion. In 110 patients with paired (pre‐ and post‐drainage) chest X‐rays and 32 patients with paired computed tomography scans, post‐drainage imaging did not provide additional information that would have influenced the clinical decision‐making process.